A case report of severe combined immunodeficiency: Masquerading as sepsis - Dhal, Subhranshu sekhar; Sagar, Hiremath; Aggarwal, Rajiv; Sapare, Anil Kumar; kekatpure, Minal (Indian Journal of Child Health, 2022)
Severe combined immunodeficiency (SCID) is a rare genetic disorder caused by diverse genetic mutations which lead to the absence or defective T cell, B cell, and Natural killer cell functions. It is usually present in the first 6 months of life and is caused by 20 different mutations. SCID defined by their cellular phenotypes such as T-B+NK+, T-B-NK-, T-B+NK-, and T-B-NK+. Various manifestations are sepsis, disseminated tuberculosis following the Bacillus Calmette–Guerin vaccine, candidiasis, Pneumocystis carinii pneumonia, severe viral infections, chronic diarrhea, failure to thrive, and malabsorption. We report a case of T-B+NK- SCID in a 5-month-old male child, who presented with fever, rash, and loose stool, and the diagnosis was confirmed by whole-exome sequencing.